INTEGRASI INSTRUMEN ISLAMIC SOCIAL FINANCE DALAM MENDUKUNG EKONOMI SIRKULAR: ANALISIS LITERATUR DAN KERANGKA KONSEPTUAL - Fahmi, Rizqi Anfanni (Moneta: Jurnal Manajemen & Keuangan Syariah, 2025)
This study explores the potential integration of Islamic Social Finance (ISF) within the circular economy framework, aiming to contribute to sustainable environmental and social development. The research investigates how instruments such as zakat, waqf, and infaq can be utilized to finance projects that promote resource management, waste reduction, and renewable energy initiatives. The methodology employed is a narrative literature review, focusing on high-quality academic sources from Scopus to synthesize existing knowledge and identify gaps in the current literature. The findings reveal that ISF, particularly zakat and waqf, can play a crucial role in financing sustainable projects. These instruments are shown to have significant potential in supporting environmental sustainability efforts, such as waste management and energy solutions. Furthermore, the integration of financial technologies, such as blockchain, is highlighted as a means to improve the transparency and efficiency of managing ISF funds for green projects. However, challenges such as insufficient regulatory frameworks, limited public awareness, and low participation in sustainability initiatives remain barriers to fully harnessing ISF’s potential in the circular economy. This research contributes to the existing body of knowledge by developing a conceptual framework that connects ISF with the circular economy. The study underscores the importance of enhancing policy support and increasing societal engagement to maximize the effectiveness of ISF in achieving environmental and social sustainability. Further empirical research is recommended to validate the proposed models and explore practical applications in diverse regions and sectors.